A Framework for Developing Antiracist Medical Educators and Practitioner–Scholars. (January 2022) - Sotto-Santiago, Sylk; Poll-Hunter, Norma; Trice, Traci; Buenconsejo-Lum, Lee; Golden, Sherita; Howell, Joy; Jacobs, Nicole; Lee, Winona; Mason, Hyacinth; Ogunyemi, Dotun; Crespo, Waleska; Lamba, Sangeeta
Abstract : With an increasing awareness of the disparate impact of COVID-19 on historically marginalized populations and acts of violence on Black communities in 2020, academic health centers across the United States have been prioritizing antiracism strategies. Often, medical students and residents have been educated in the concepts of equity and antiracism and are ready to tackle these issues in practice. However, faculty are not prepared to respond to or integrate antiracism topics into the curriculum. Leaders in faculty affairs, education, diversity, and other departments are seeking tools, frameworks, expertise, and programs that are best suited to meet this imminent faculty development need. In response to these demands for guidance, the authors came together to explore best practices, common competencies, and frameworks related to antiracism education. The focus of their work was preparing faculty to foster antiracist learning environments at traditionally predominantly White medical schools. In this Scholarly Perspective, the authors describe their collaborative work to define racism and antiracism education; propose a framework for antiracism education for faculty development; and outline key elements to successfully build faculty capacity in providing antiracism education. The proposed framework highlights the interplay between individual learning and growth and the systemic and institutional changes needed to advance antiracist policies and practices. The key elements of the framework include building foundational awareness, expanding foundational knowledge on antiracism, embedding antiracism education into practice, and dismantling oppressive structures and measuring progress. The authors list considerations for program planning and provide examples of current work from their institutions. The proposed strategies aim to support all faculty and enable them to learn, work, and educate others in an antiracist learning environment. Abstract : Supplemental Digital Content is available in the text.